2015
DOI: 10.4081/monaldi.2010.276
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Early Outcome of Prolonged Mechanical Ventilation in Contemporary Heart valve Surgery

Abstract: Predictors and Early Outcome of ProlongedResults: PMV occurred in 6.6% of patients. Initial ventilation hours, atrial fibrillation, cardiac arrest and reintubation were the most prevalent postoperative complications. Preoperative renal failure, postoperative stroke, intra aortic balloon pump insertion, emergent operation, complete heart block, longer perfusion time were independent predictors of PMV in our patients.Conclusion: PMV is associated with significant comorbidities and increased hospital mortality. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
7
0
10
Order By: Relevance
“…This failure rate is higher than that reported in other studies (1), most likely because our study was performed in a cardiac surgery referral center and included severely ill patients, as shown by the high EuroSCOREs (22). The patients who had weaning failure in our study may have developed myocardial dysfunction secondary to CPB.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This failure rate is higher than that reported in other studies (1), most likely because our study was performed in a cardiac surgery referral center and included severely ill patients, as shown by the high EuroSCOREs (22). The patients who had weaning failure in our study may have developed myocardial dysfunction secondary to CPB.…”
Section: Discussionmentioning
confidence: 54%
“…The failure to wean from mechanical ventilation after cardiac surgery is associated with worse outcomes, including increased length of hospital stays and higher costs (1-3). In a prospective study of 885 patients who underwent coronary artery bypass grafting (CABG), Wong et al (4) identified increased age, female gender, the postoperative use of an intra-aortic balloon pump (IABP), the use of inotropes, bleeding, and atrial arrhythmia as risk factors for weaning failure and prolonged mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Tem sido observado na literatura científica, o predomínio de mulheres idosas com comorbidades variadas, submetidas a cirurgias cardíacas, em especial troca de válvula. [9][10][11] O conhecimento das variavéis sociodemográficas, clínicas e cirúrgicas dos indivíduos submetidos à cirurgia cardíaca são essenciais para o planejamento de qualidade da assistência de enfermagem. 5,[11][12][13] Tendo em vista que diversos destes aspectos podem contribuir para aumentar o tempo de permanência em Unidade de Terapia Intensiva (UTI) e tempo de ventilação mecânica.…”
Section: Discussionunclassified
“…Da mesma forma, a cirurgia cardíaca prévia é um fator independente para VM prolongada, o que resulta em maior tempo de permanência do paciente no leito. [9][10]17 Assim, estudos anteriores realizados com pacientes no pós-operatório de cirurgia cardíaca elencaram diagnósticos iguais aos do presente estudo, entre eles: mobilidade física prejudicada, débito cardíaco diminuído, hipotermia, comunicação verbal prejudicada, risco de integridade da pele prejudicada, risco de queda, risco de aspiração, risco de infecção e integridade tissular prejudicada. 5,18 O diagnóstico Risco de Infecção tem alta prevalência em pacientes submetidos à cirurgia cardíaca, possivelmente, relacionado à necessidade de procedimentos invasivos, como por exemplo: cateterismo vesical, acesso venoso central, drenos de tórax e mediastino, acesso arterial para pressão arterial média, além da destruição dos tecidos e das defesas primárias.…”
unclassified
“…Prapas et al 11 concluded that periop need IABP insertion is also an independent risk factor of delayed extubation after CABG surgery. According to Shirzadet al 24 atrial fibrillation, sudden cardiac arrest and need for intubation are common risk factors of delayed extubation after valvular heart surgery. So different researchers have found different risk factors of delayed extubation after cardiac surgery.…”
Section: Early Extubation (N=55) Delayed Extubation (N=26) P-valuementioning
confidence: 99%